Survival following accidental scarf strangulation. (September 2016) - Shetty, Ullasa; Deepak, M; Hussain, Syed Ather; Usmani, Hadi; Osama, Muhammad; Pereira, Kiran Godwin; Menezes, Ritesh George
Injury or death by strangulation, unless otherwise explained, is almost always homicidal. Accidental strangulation may occur but only very rarely. We present such a case of accidental strangulation and survival in a motorbike pillion rider. A long scarf ( dupatta ) clad woman, sitting at the back of a two wheeler motorbike, fell after her long scarf got caught in the back wheel. The lady was first taken to a local clinic and then later was referred to a hospital for a suspected spine injury where she made an uneventful recovery. This case report exposes the precarious position of women pillion riders wearing a long scarf and emphasizes the need for extra caution and the need for wheel guards on spoked wheels in particular.